Analyse du site de Podcast Français Facile comme support d’initiation à l’apprentissage de la grammaire introductif - Silmi Nusaibah; Tri Eko Agustiningrum (Universitas Negeri Semarang, 2024)
Language learning sites through internet media are a new form to provide convenience in gaining knowledge in various fields, one of which is in the field of language, namely French, which can be used as one of the learning media. The purpose of this study is to determine the classification of beginner-level Grammaire material contained in the Français Facile Podcast site and then describe and analyze its suitability to be used as a supporting medium for Grammaire Introductif learning. This study uses a qualitative descriptive approach by analyzing material using data cards and triangulation tables to analyze and calculate the amount of material contained in the introductive RPS grammaire. The results showed that the introductive grammaire material on the Français Facile Podcast site adapted to RPS material contained a total of 41 materials, and 12 materials were not found on this site. So, it can be concluded that the site can be used as a supporting medium in learning introductive Grammaire courses at the beginner level.